TINJAUAN ASAS UNDANG-UNDANG PERLINDUNGAN KONSUMEN (UUPK) TERHADAP PROSES PENGEMBALIAN DANA KONSER BOY PABLO: Consumer Protection Act (UUPK) Principles Review of the Boy Pablo Concert Fund Refund Process - Hagya Paramarizky Marsaoleh; Sharda Abrianti (Reformasi Hukum Trisakti, 2025)
In 2022, a concert organized by the promoter Kultvizion inviting a band from Norway, Boy Pablo. However, the concert was canceled because Boy Pablo band was unable to attend the concert. The he problem is whether the process of returning funds from the Boy Pablo concert is in accordance with the principles of justice and legal certainty based on Law Number 8 of 1999 concerning Consumer Protection (UUPK). This research is normative legal research based on secondary data supported by interviews. Data analysis was carried out qualitatively and conclusions were drawn using deductive logic. The results showed that business actors gave false statements and misled the consumers so Kultvizion had violated Article 8 letter (f) of the UUPK and was sanctioned in accordance with Article 62 para. (1) of the UUPK. The conclusion is of the analysis from this research are that there is a mismatch in the principles of justice and legal certainty based on Law Number 8 of 1999 concerning Consumer Protection (UUPK).